Guessing as a Word-Solving Strategy: Contributing a Little for Understanding a Text with Unfamiliar Low Frequency Words - Siusana Kweldju (TEFLIN, 1998)
Abstract: This paper reports the results of a study that investigated the effectiveness of guessing as a word-solving strategy. Conducted to 32 non-native English language teacher trainees, this study disÃÂcovered that with a vocabulary size of 3526 word families, students were able to recognize high frequency words, but unable to correctly guess the meanings of low frequency ones. In addition, they used inunediate instead of global contexts in their guesses. Consequently, holistic comprehension could not be made. Students were also too confident with their guesses. When they thought that they knew the meaning of a word, they might not know it correctly. This study sugÃÂgests that using dictionaries and contrived learning of vocabulary are crucial for the bredth and the depth of vocabulary. Students also need some training for improving their word guessing strategy.